The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31557/apjcp.2021.22.8.2437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trismus and Its Impact on Oral Health-Related Quality of Life in Patients Treated for Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma, one of the most common malignancies, has a poor prognosis due to impairment in oral functions secondary to treatment. Trismus one of the major causes of impairment of oral function. The present study investigated the prevalence of trismus and its impact on oral health-related quality of life (OHRQoL) in patients treated for oral squamous cell carcinoma (OSCC). The maximum inter-incisal mouth opening of hundred OSCC patients was recorded at post-treatment and 3 months post-treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The authors reported that patients presenting with RIT had significantly lower head and neck-specific quality of life in terms of social contact, sexuality, teeth, mouth opening, dry mouth, feeling ill, nutritional supplement, and weight loss. Lee's findings were consistent with those of previous research, 37,43,44 all of which confirm the negative effects of RIT on all domains of quality-of-life measures. Hence, if backed up with further research findings, the risk classification introduced here might aid in the prompt implementation of risk-based preventive and/or therapeutic strategies, thus lowering the occurrence of highly debilitating RIT and its negative impacts in some patient groups, particularly the intermediate and high-risk patients.…”
Section: Discussionsupporting
confidence: 89%
“…The authors reported that patients presenting with RIT had significantly lower head and neck-specific quality of life in terms of social contact, sexuality, teeth, mouth opening, dry mouth, feeling ill, nutritional supplement, and weight loss. Lee's findings were consistent with those of previous research, 37,43,44 all of which confirm the negative effects of RIT on all domains of quality-of-life measures. Hence, if backed up with further research findings, the risk classification introduced here might aid in the prompt implementation of risk-based preventive and/or therapeutic strategies, thus lowering the occurrence of highly debilitating RIT and its negative impacts in some patient groups, particularly the intermediate and high-risk patients.…”
Section: Discussionsupporting
confidence: 89%
“…This observation emphasizes the importance of surgical innovation in enhancing treatment accessibility and effectiveness for patients facing complex clinical presentations. According to previous studies, some mechanisms may further explain the worse survival outcomes in oral cancer patients with trismus [ 9 , 26 , 27 , 28 ]. The potential impact of trismus on overall survival may be mediated through the emergence of dysphagia, culminating in malnutrition and the risk of aspiration [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, this condition is particularly prevalent among those who habitually chew betel quid, a practice known to contribute to oral submucosal fibrosis (OSMF) and oral cancer risk [ 6 , 7 ]. While the debilitating effects of post-treatment trismus on patients’ quality of life are well documented [ 8 , 9 ], the impact of preoperative trismus on surgical outcomes in oral cancer patients, particularly those undergoing transoral robotic surgery (TORS), remain underexplored. This oversight persists despite evidence suggesting that preoperative trismus, irrespective of the surgical method, poses significant challenges to surgical access [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rather surprising finding in this study was the substantially lower rate of postoperative trismus among patients who received preoperative immunotherapy. Trismus is a common adverse effect of head and neck cancer treatment and is a distressing symptom that can drastically diminish one’s quality of life . Trismus from surgery results from the disruption of the muscles of mastication, particularly the pterygoids, or the temporomandibular joint.…”
Section: Discussionmentioning
confidence: 99%